A positive feedback loop of the TAZ/β-catenin axis promotes Helicobacter pylori-associated gastric carcinogenesis - Xu, Xinbo; Shu, Chunxi; Wu, Xidong; Ouyang, Yaobin; Cheng, Hong; Zhou, Yanan; Wang, Huan; He, Cong; Xie, Chuan; He, Xingxing; Hong, Junbo; Lu, Nonghua; et al. (Frontiers in Microbiology, 2022)
Background: H. pylori infection is the strongest known risk factor for gastric cancer. The Hippo signaling pathway controls organ size and maintains tissue homeostasis by coordinately regulating cell growth and proliferation. Here, we demonstrate the interactive role of TAZ, the transcriptional coactivator of the Hippo pathway, and beta-catenin in promoting the pathogenesis of H. pylori infection. Methods: Expression of TAZ in human gastric tissues and H. pylori-infected INS-GAS mice were evaluated. Western blot, immunofluorescence, immunohistochemistry, and RT-PCR assays were performed. Co-immunoprecipitation was performed to examine TAZ interaction with β-catenin. TAZ and β-catenin were silenced using small interfering RNAs. HA-beta-catenin and Flag-TAZ were constructed. Results: Increased TAZ was noted in human gastric cancer tissues compared to chronic gastritis tissues and in H. pylori-positive gastritis tissues compared to H. pylori-negative gastritis tissues. in addition, H. pylori infection induced TAZ expression and nuclear accumulation in the gastric tissue of INS-GAS mice and cultured gastric epithelial cells, which was dependent on the virulence factor CagA. Moreover, knockdown of TAZ or β-catenin significantly suppressed H. pylori infection-induced cell growth, survival, and invasion. Furthermore, the interactive regulation of activation between TAZ and β-catenin was revealed. Finally, β-catenin was required for H. pylori-induced TAZ activation. Conclusions: These findings suggest that there is a positive feedback loop of activation between TAZ and β-catenin that could play an important role in CagA+H. pylori infection-induced gastric carcinogenesis. TAZ inhibition might be a potential target for the prevention of H. pylori infection-associated gastric cancer.